PENGARUH PEMASANGAN MAGIC RING PADA EXHAUST MANIFOLD TERHADAP KONSUMSI BAHAN BAKAR SEPEDA MOTOR YAMAHA VEGA RR TAHUN 2014 DENGAN MENGGUNAKAN VARIASI BAHAN BAKAR - Setyo Sri Haryono; Ranto Ranto; Husin Bugis (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2020)
Vehicle technology is still not effective in saving fuel consumption. Various attempts have been made to reduce fuel consumption in motorized vehicles. This is done to prevent the depletion of the availability of fossil energy, especially petroleum. One of the emerging technological innovations is the Magic ring. Magic ring is a technology to reduce fuel consumption by reducing the diameter of the exhaust manifold channel with a special design. This study aims to determine the effect of the use of the Magic ring on the fuel consumption of motorized vehicles (gasoline engines). This study used an experimental method on a single cylinder 110cc four-stroke gasoline motorcycle engine. This study uses three types of fuel, RON 90, RON 92, and RON 98 for fuel consumption in ml / minute, and data analysis using quantitative descriptive. The results of this study are looking for the most efficient fuel consumption in each type of fuel at 1500 rpm. The results show that there is an effect of installing a Magic ring in saving fuel consumption. Evidence of this is the increase in the value of fuel consumption savings with a percentage of 23.3% at RON 90, 21.5% at RON 92, 19.4% at RON 98. The test results show that the installation of Magic rings is effective in reducing fuel consumption and can used in the future to save fuel.